2022
DOI: 10.5296/jsss.v8i2.19488
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and Socialization in the Days of the Covid-19 Pandemic Crisis Research Analysis and Suggestions

Abstract: The Covid-19 pandemic, already completing almost two years of its irreversible course of action, has exerted and still exerts significant pressures on the social and economic systems of countries worldwide as well as on human relations. Human friendship and socialization, as key factors of human coexistence and cooperation within a social group, have been hit hard by the strict imposition of measures of distancing and social isolation in order to limit the disease and stop its unexpectedly deadly transmission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…However, the social support was weakened during the COVID-19 pandemic (Elmer et al, 2020). As a result, the central position of individual friendship network will be affected (Diamanti et al, 2021).…”
Section: Self-efficacy and Friendship Networkmentioning
confidence: 99%
“…However, the social support was weakened during the COVID-19 pandemic (Elmer et al, 2020). As a result, the central position of individual friendship network will be affected (Diamanti et al, 2021).…”
Section: Self-efficacy and Friendship Networkmentioning
confidence: 99%
“…In the context of education, the most suitable option for continuing learning after the forced closure of all educational institutions was judged worldwide to be distance education. In higher education, digital platforms supported the new form of learning (e-learning) in order to continue academic courses [2], while on a social level, through networks of friends, students tried to maintain student connection and socialisation in the context of psychological empowerment, marginalising the adverse effects of the imposition of quarantine [12]. However, despite the efforts, the interruption of live teaching had negative consequences for the students.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys conducted among the student population showed that the lock down and the forced confinement in the family environment, caused serious symptoms of anxiety and depressive episodes in the psyche of the young people [8,[12][13][14][15][16] affecting their learning mood and engagement as well as performance [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%